METODE PEMANTAUAN EKSPLOITASI DAN REKLAMASI TAMBANG BATUBARA MENGGUNAKAN DATA SENTINEL-2 - Samsul Arifin (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2020)
Abstract: Mining is an activity of extracting non-renewable natural resources, including coal. Mining cannot be separated from the aspect of the company, because the principle has the aim to be utilized to the community in meeting their needs. In realizing this mining activities must be optimally managed and utilized for the present and future. Monitoring and supervision of mining activities effectively and efficiently can be used technology that has data with wide scope and availability on an ongoing basis. Remote sensing technology has the capability above requirements used are Sentinel-2. Sentinel-2 has adequate spectral, spatial and temporal resolution. The purpose of this study was to develop a monitoring model for coal mine exploitation using Sentinel-2 data. Detection of geobiophysical parameters is a model for extracting changes in the earth's surface due to mining activities. Processing techniques and formulas that can be used to identify and monitor the phenomenon of changes in the earth's surface include the Normalized Difference Vegetation Index and Normalized Burn Ratio.